FACTORS DETERMINING USE OF INTERNATIONAL FINANCIAL REPORTING STANDARDS FOR SMALL TO MEDIUM SIZE ENTITIES (IFRS FOR SMES) IN ZIMBABWE - Moyo, Sherman; Mpofu, Favourate Y (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Small and medium enterprises are the backbone of most African economies, contributing significantly to economic growth, employment creation, and sustainable development in these economies, yet the SMEs face survival challenges, with few going beyond five years. In Zimbabwe, SMEs drive employment creation, contribute to the gross domestic product (GDP), and promote livelihoods, alleviating poverty in a country where the formal sector is dwindling. As the country struggles to address economic challenges and strives to promote economic growth, the adoption of the IFRS for SMEs is pivotal for enhancing transparency, strengthening domestic revenue mobilization, attracting investment, and facilitating access to financing. This study investigates the factors influencing the adoption of International Reporting Standards for SMEs (IFRS for SMEs) in Zimbabwe. The research addresses a gap in the literature by comprehensively identifying factors that impact the adoption of the IFRS for SMEs reporting framework in a developing economy. This research utilizes stratified and cluster sampling techniques. The findings reveal that the needs of financial statement users, the legal structure of an SME, the level of accounting expertise within an SME, and the outsourcing of accounting services are key determinants of IFRS for SMEs usage in Zimbabwe. Keywords: IFRS; SMEs; Financial Statement; Zimbabwe